Quantification of Aloin in Aloe barbadensis Miller Leaf Gel and Latex from Selected Regions of Kenya - Nakiguli, Caroline K.; Kosgei, Viola J.; Cherutoi, Jackson K.; Odda, John (Open Access Library Journal, 2022)
Aloe barbadensis Miller (A. barbade nsis ) has been reported for use in the traditional management of malaria in Kenya. Aloin (an anthraquinone-C-gly- coside) is one of the therapeutic molecules in Aloe species that is responsible for their antimalarial effect. However, there is no report on the aloin content of A. barbadensis leaves latex and gel from Kenya. This study, therefore, isolated and quantified aloin levels in Phosphate Buffered Saline (PBS) extracts of A. barbadensis leaf gels and latexes sampled from Kisumu, Elgeyo-Marakwet and Baringo Counties of Kenya. Aloin was isolated by preparative thin layer chromatography and then subjected to thin layer chromatography and quantified using High-Performance Liquid Chromatography (HPLC). Results sh- owed that the highest aloin content of 237.971 ± 5.281 mg aloin/g DW was for dry latex from Elgeyo-Marakwet followed by those from Baringo (198.409 ± 2.000 mg aloin/g DW) and then Kisumu (40.760 ± 0.088 mg aloin/g DW). Latexes had comparatively low aloin contents, and followed the order Kisumu > Baringo > Elgeyo-Marakwet. The HPLC method validation was satisfactory and exhibited adequate linearity, repeatability and accuracy. The HPLC method developed for identification and quantification of aloin in A. barbadensis leaves had high sensitivity, is specific, and the mobile phase systems and sample preparation method are simple. This can be used for quality control of Kenyan Aloe extracts. The results indicated intraspecific variation in aloin content of A. barbadensis leaf gels and latexes from different regions of Kenya.
Keywords: Aloe vera; Aloin; High-Performance Liquid Chromatography; Kenya